Indicadores físicos, químicos e biológicos da qualidade do solo em sistemas agroflorestais agroecológicos na área de preservação ambiental Serra da Mantiqueira, MG - Camargo, Flora Ferreira (2016)
Serra da Mantiqueira is a protected area that comprises an ecosystem considered a priority for biodiversity conservation and is constantly threatened by human activity. The adoption of Agroforestry Systems has improved livelihood, reduced the pressure on protected ecosystems and integrated landscape conservation. However, there is still lack of information regarding these models. Our objective was to assess soil quality of Agroforestry systems in this region in order to build a tool to support decision making when farmers want to convert their production. We conducted two independent studies: one to characterize this model as a reference productive unit, in order to incentivize its adoption in the region; and another to assess the changes in soil attributes in these systems. We evaluated two agroforestry systems three- and six-year old, compared them to Olive tree plantations, pastures and an area under natural regeneration dominated by ferns, having a native forest as the reference ecosystem. Then, we calculated indices to estimate soil quality, using the method developed by Velásquez et al. (2007). We performed routine soil analyzes and tested for correlations between attributes and each management system using multivariate analyzes. Our results showed that the agroforestry systems had good soil quality compared to the reference ecosystem, notably soil density and aggregate stability. Regarding the chemical attributes, we can infer that fertility level related to organic matter content in the agroforestry systems is similar to the reference ecosystem, indicating the benefits of agroecological management. The grouping analyzes related to the chemical and physical properties of soils indicated these systems tend to achieve sustainability. The six-year old agroforestry system was closer to the reference ecosystem and may have appropriate conditions for colonization by soil fauna that presented higher transformation capacity and resilience within these systems. The native forest showed the highest index for soil quality, followed by the six-year old agroforestry system. Therefore, we conclude that the agroforestry systems have the capacity to improve soil quality in this region, approaching the conditions in the reference ecosystem along time. The management and implementation of this agroforestry model showed to have potential for soil quality restora tion and could substitute, as a sustainable production alternative, the areas dominated by Pteridium in Serra da Mantiqueira.